2011
DOI: 10.3344/kjp.2011.24.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Participation of KATP Channels in the Antinociceptive Effect of Pregabalin in Rat Formalin Test

Abstract: BackgroundPregabalin is an anticonvulsant and analgesic agent that interacts selectively with the voltage-sensitive-Ca2+-channel alpha-2-delta subunit. The aim of this study was to evaluate whether the analgesic action of intrathecal (IT) pregabalin is associated with KATP channels in the rat formalin test.MethodsIT PE-10 catheters were implanted in male Sprague-Dawley rats (250-300 g) under inhalation anesthesia using enflurane. Nociceptive behavior was defined as the number of hind paw flinches during 60 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Intrathecal administration of pregabalin, through catheterization of spinal subarachnoid space, was shown to decrease formalin-induced frequency of flinching in a dose dependent manner. However, administration of glibenclamide reversed the analgesic effect of pregabalin suggesting that the anti-nociceptive effect of pregabalin in the rat formalin test may be associated with activation of K ATP channels [ 114 ]. Earlier studies had shown that application of pregabalin to the intracellular surface of the excised patches activates K ATP channels in the differentiated hippocampal neuron-derived H19-7 cells, suggesting that its binding side could be primarily on the intracellular site [ 115 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Intrathecal administration of pregabalin, through catheterization of spinal subarachnoid space, was shown to decrease formalin-induced frequency of flinching in a dose dependent manner. However, administration of glibenclamide reversed the analgesic effect of pregabalin suggesting that the anti-nociceptive effect of pregabalin in the rat formalin test may be associated with activation of K ATP channels [ 114 ]. Earlier studies had shown that application of pregabalin to the intracellular surface of the excised patches activates K ATP channels in the differentiated hippocampal neuron-derived H19-7 cells, suggesting that its binding side could be primarily on the intracellular site [ 115 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…There is evidence that the opening of K ATP channels participates in the analgesic effect of the non-steroidal anti-inflammatory drugs ketorolac [ 16 ] and diclofenac [ 17 , 18 ], but not in that of indomethacin [ 17 ]. There is also evidence that K ATP channels play a role in the analgesic effect of a variety of agents such as morphine [ 19 ], clonidine [ 20 ] and 5-HT1 agonists [ 21 ], atrial natriuretic peptide (ANP) [ 17 ], and pregabalin [ 22 ]. Therefore, it appears that the opening of K ATP channels is a common mechanism of antinociception.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the results of our study in which we found that pregabalin 100 mg/kg decreased the number of writings in acetic acidinduced writhing test in mice. Furthermore, other investigators examined the antinociceptive effect of pregabalin in rat formalin pain model [25]. They found that intratechal pregabalin exhibited antinociceptive effect.…”
Section: Discussionmentioning
confidence: 98%